PENGEMBANGAN MODUL ELEKTRONIK BERBASIS WEBSITE UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS XI SMAN 11 SAROLANGUN - Sari, Dwi Kartika; Kusnadi, Edy; Idarianty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop and examine the feasibility, practicality, and effectiveness of a website-based electronic module on narcotics to improve the learning motivation of Grade XI senior high school students. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were Grade XI students of SMAN 11 Sarolangun, divided into an experimental class and a control class. Research instruments included expert validation questionnaires, teacher and student practicality questionnaires, and a learning motivation questionnaire. Data were analyzed using descriptive quantitative analysis and inferential statistics through an independent samples t-test. The results showed that the developed website-based electronic module was categorized as highly feasible based on evaluations by material, media, and language experts, and highly practical according to teachers’ and students’ responses. The effectiveness test indicated that students in the experimental class demonstrated higher learning motivation than those in the control class. Statistical analysis revealed a significance value of 0.000 (p < 0.05), indicating a significant difference in learning motivation between the two groups. Therefore, the website-based electronic module is effective as a learning medium to enhance students’ learning motivation.